Antimicrobial stewardship program at a tertiary care academic medical hospital: Clinical, microbiological and economic impact. A 5-year temporary descriptive study. Issue 2 (June 2020) - Jover-Sáenz, Alfredo; Ramírez-Hidalgo, María Fernanda; Vidal, Montserrat Vallverdú; González, Merce García; Cano Marrón, Santiago Manuel; Arias, Alfredo Escartín; Sacrest, Miquel Falguera; Castellana-Perelló, Dolors; Barcenilla-Gaite, Fernando; ,
Abstract: Introduction: Few prospective studies analyze, with sufficient duration, the impact of an antimicrobial stewardship program (AMSP) carried out entirely in a hospital. Methods: Descriptive study evaluating the consumption of antimicrobials expressed in defined daily doses (DDD) per 100 hospital occupied bed-days (OBDs) stratified in medical, surgical and intensive care unit (ICU) and the incidence of densities (ID) per 1, 000 hospital OBDs of the prevalent multidrug-resistant organisms (MDRO) in a tertiary hospital, over a period of 5 years before and after the implementation of an AMSP. Analysis of direct costs and those associated with hospital stay and mortality. Results: A total of 32, 802 patients with antibiotic treatment were included in the intervention period (2013–2017). Non-imposed advice was exercised in 14.9%. The degree of adherence to recommendation was 87.9%, direct treatment and de-escalation being the most frequently admitted interventions ( P <0.001). Overall hospital consumption of antibacterials in DDD/100s decreased by 5.7% (77.04 vs. 71.33) between 2008 and 2017. In ICU, the average DDD/100s showed a reduction from 155 to 113 (mean difference -18, P =0.005). There was a decrease in the DI/1000 OBDs of MDROs in the post-intervention period (RR 0.78; CI 95% [0.73, 0.84], P <0.001). The average annual cost of antibacterials declined from €1, 435, 048 to €955, 805 (mean difference -€469, 243; P =0.001). Conclusion: Long-term maintenance of a hospital AMSP was associated with a reduction in antibiotic consumption, especially in ICU, as well as a beneficial ecological impact and economic savings.